An Event-related Potential Study on the Interaction between Lighting Level and Stimulus Spatial Location - Carretié, Luis; Ruiz-Padial, Elisabeth; Mendoza, María T. (Frontiers in Human Neuroscience, 2015)
Due to heterogeneous photoreceptor distribution, spatial location of stimulation is crucial to study visual brain activity in different light environments. This unexplored issue was studied through occipital event-related potentials (ERPs) recorded from 40 participants in response to discrete visual stimuli presented at different locations and in two environmental light conditions, low mesopic (L, 0.03 lux) and high mesopic (H, 6.5 lux), characterized by a differential photoreceptor activity balance: rod>cone and rod<cone, respectively. Stimuli, which were exactly the same in L and H, consisted of squares presented at fixation, at the vertical periphery (above or below fixation) or at the horizontal periphery (left or right). Analyses showed that occipital ERPs presented important L vs. H differences in the 100 to 450 millisecond window, which were significantly modulated by spatial location of stimulation: differences were greater in response to peripheral stimuli than to stimuli presented at fixation. Moreover, in the former case, significance of L vs. H differences was even stronger in response to stimuli presented at the horizontal than at the vertical periphery. These low vs. high mesopic differences may be explained by photoreceptor activation and their retinal distribution, and confirm that ERPs discriminate between rod- and cone-originated visual processing.